Anticancer activity of sodium caffeate and its mechanism - Xu Feng; Zhang Sheng-hua; Shao Rong-guang; Zhen Yong-su (Acta Pharmacologica Sinica, 2016)
Aim: To study the anticancer activity of sodium caffeate (SC). Methods: A nucleoside transport assay was used to analyze the inhibitory effects of SC on nucleoside rescue. The MTT assay was used to measure cell proliferation. Flow cytometry was used to measure the apoptosis of BEC-7402 induced by SC and the cell cycle distribution change. Western blotting analysis was employed to investigate Bcl-2, caspase and Bax expression. Intracellular Ca2+ and mitochondrial membrane potential were determined by flow cytometry. In vivo anti-tumor activity was measured using a tumor transplantation model in mice. Results: SC inhibited the nucleoside transport of BEL-7402 cells with an IC50 of 1.02 mg/mL. SC inhibited tumor cell proliferation with an IC50 between 100 mug/mL and 200 mug/mL. SC induced BEL-7402 cell apoptosis in a time- and dose-dependent manner, which was induced by arresting cells in S phase. The in vivo study showed that tumor growth was inhibited in a dose-dependent manner. Activated caspase-3 and Bax expression were up-regulated after treatment with SC, while Bcl-2 expression was down-regulated. Intracellular Ca2+ was increased while mitochondrial membrane potential was decreased by SC. Conclusion: SC is a new anticancer agent with promising potential.